Rabbit tumor necrosis factor: mechanism of action. - Ruff, M R (1981)
Rabbit tumor necrosis factor (TNF) was examined for effects on normal and transformed cells in culture. Several assays for killing of L-929 cell targets were developed, and their sensitivities were compared. Normal cells were not killed by TNF, and the discrimination between normal and transformed cells was shown not to be due to a cell cycle-dependent mechanism. TNF killing of L-929 cells was delayed for 10 to 12 h and thereafter showed concentration and time-dependent increases in cytolysis. Actinomycin D or cycloheximide treatment of L-929 cells resulted in an enhancement of the rate of cell killing as well as a shortening of the preceding lag period. TNF killing of L-929 cells was temperature dependent; cells were considerably more resistant to lysis at 25 degrees C and showed enhanced killing at 39 degrees C as compared to 37 degrees C controls. The slope of the dose curve showed less than single-hit kinetics. A model for cell killing whose general features incorporate both the specificity and catalytic properties of an enzymatic reaction is proposed for TNF action.